2021
DOI: 10.3390/pharmaceutics13060908
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of Ursolic Acid Loaded into Nanostructured Lipid Carriers in Experimental Visceral Leishmaniasis

Abstract: Ursolic acid, a triterpene produced by plants, displayed leishmanicidal activity in vitro and in vivo; however, the low solubility of this triterpene limits its efficacy. To increase the activity of ursolic acid (UA), this triterpene was entrapped in nanostructured lipid carriers (UA-NLC), physical-chemical parameters were estimated, the toxicity was assayed in healthy golden hamsters, and the efficacy of UA-NLC was studied in experimental visceral leishmanisis. UA-NLC exhibited a spherical shape with a smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The efficient delivery of ursolic acid from lipid nanoparticles stimulated expression of IFN-g and iNOS, and boosted the production of leishmania-specific IgG antibodies. Although no comparison was made with LAmpB treatment, it is clear that the encapsulation of ursolic acid offers a superior drug formulation with reduced toxicity and increased parasiticidal effect (Jesus et al, 2021).…”
Section: Leishmaniasismentioning
confidence: 99%
“…The efficient delivery of ursolic acid from lipid nanoparticles stimulated expression of IFN-g and iNOS, and boosted the production of leishmania-specific IgG antibodies. Although no comparison was made with LAmpB treatment, it is clear that the encapsulation of ursolic acid offers a superior drug formulation with reduced toxicity and increased parasiticidal effect (Jesus et al, 2021).…”
Section: Leishmaniasismentioning
confidence: 99%
“…Jesus et al observed that the compound was loaded into nanostructured lipid carriers (UANLC), and L. infantum infected golden hamsters cured with the nanocomposition, which showed no morphological alterations in their visceral tissues ( 37 ). AST, ALT, urea and creatinine were not abnormal.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the reduction of parasitic load in UA-NLC-treated hamsters was more significant than the ursolic acid-free group and the amphotericin B group. Furthermore, the beneficial activity of UANLC was linked with an increased protective immune response and a high preservation level of the spleen and liver as well as the normalization of liver and kidney functions ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 15 also inhibits the growth of P. falciparum cultured in human erythrocytes (Tallorin et al, 2014) et al, 2021). This compound also demonstrated moderate activity against promastigotes of L. infantum and, L. amazonensis as well as T. cruzi amastigotes (de Jesus et al, 2021;Machado et al, 2018).…”
Section: Terpenes Active Against Visceral Leishmaniasismentioning
confidence: 91%
“…The study discovered a raised transcription of IFN-γ mRNA and expression of inducible nitric oxide synthase (iNOS) in animals treated with 6-NLC. This may partly explain the observed leishmanicidal activity (Jesus et al, 2021). In a different study, 6-NLC coated with chitosan oligosaccharide performed impressively against Leishmania in vitro and BALB/c mice with L. donovani infection.…”
Section: Leishmaniasismentioning
confidence: 93%